Trends and new business models in the portuguese fashion industry: a strategic innovation perspective - Queirós, David (2013)
This research project focuses on the discussion of trends and new business models for the textile and clothing industry in general and for the fashion industry, in particular, using tools and an approach supported on strategic innovation. A documentary analysis was performed and they were conducted a series of semi-structured interviews. It was noted the importance of the strategic analysis and particularly strategic innovation for the design of new successful business models. Main findings and results are presented on the basis of two main criteria: relevance and feasibility. Two generic strategies were identified.